Informed consent, gatekeepers and go-betweens: negotiating consent in child and youth-orientated institutions - Heath, Sue; Charles, Vikki; Crow, Graham; Wiles, Rose (British educational research journal, 2007)
Gaining informed consent from research participants is widely regarded as central to ethical research practice. This article reports on research which sought to identify contemporary practice in this area amongst researchers working in fields where research participants are often constructed as vulnerable within the research process, and where their potential involvement tends to be mediated by institutional gatekeepers. Drawing on telephone interview and focus group data, the article focuses specifically on the experiences of researchers working with children and young people. It highlights the tensions experienced by many researchers between a personal commitment to an ethical framework which seeks to prioritise the agency and competency of children and young people, and the conditions imposed upon them by working within institutional settings where these principles may be undermined. This research suggests that the consent practices of child- and youth-orientated institutions, however much frowned upon, tend to go largely unchallenged by researchers, to the detriment of the rights of children and young people to opt in and out of research on their own behalf.